Abstrack EFEKTIVITASPENDAMPINGAN ORANG TUA SISWA SEKOLAH DASAR SELAMA BELAJAR DARI RUMAH DI KECAMATAN LANGKE REMBONG MANGGARAI NTT - Sumardi, Vinsensius; Gregorius Banase; Melkior M.P Agung; Yasinta Senol; Arlina Yuyun (JIPD (Jurnal Inovasi Pendidikan Dasar), 2022)
During the Covid 19 pandemic, many elementary schools in the Langke Rembong sub-district did not hold face-to-face learning. Fulfilling the rights of students to receive education services during the COVID-19 emergency, the learning process is carried out through the Learning from Home (BDR) process. When learning from home, parents are expected to take part and be active in assisting their children. This study aims to determine the roles and obstacles faced by parents in assisting children during learning from home. The research subjects were parents of elementary school students in Langke Rembong District, Manggarai. The method used to obtain information is a questionnaire and interviews. The results of the study show: (a) While children are learning from home, the roles that are displayed by parents include; replace the role of teachers in schools; fulfilling children's learning facilities; encouraging children to follow online learning from school, and providing direction to children. (b) Many difficulties experienced by parents in mentoring include: lack of parental knowledge regarding teaching materials for elementary school children; parent's educational background; low parental income; busy parents at work; and variations in the way parents accompany their children's learning.